Electrochemistry-Enabled Ir-Catalyzed Vinylic C–H Functionalization - Yang, Qi-Liang; Xing, Yi-Kang; Wang, Xiang-Yang; Ma, Hong-Xing; Weng, Xin-Jun; Yang, Xiang; Guo, Hai-Ming; Mei, Tian-Sheng (Journal of the American Chemical Society, 2019)
Synergistic use of electrochemistry and organometallic catalysis has emerged as a powerful tool for site-selective C–H functionalization, yet this type of transformation has thus far mainly been limited to arene C–H functionalization. Herein, we report the development of electrochemical vinylic C–H functionalization of acrylic acids with alkynes. In this reaction an iridium catalyst enables C–H/O–H functionalization for alkyne annulation, affording α-pyrones with good to excellent yields in an undivided cell. Preliminary mechanistic studies show that anodic oxidation is crucial for releasing the product and regeneration of an Ir(III) intermediate from a diene-Ir(I) complex, which is a coordinatively saturated, 18-electron complex. Importantly, common chemical oxidants such as Ag(I) or Cu(II) did not give significant amounts of the desired product in the absence of electrical current under otherwise identical conditions.